Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar IPA Peserta Didik Kelas VIII SMP - Nana Sutrisna; Petri Reni Sasmita (SPEJ (Science and Physic Education Journal), 2022)
Abstract: The purpose of this study was to determine the effect of the Problem Based Learning (PBL) model on the science learning outcomes of Class VIII students of SMP Negeri 10 Sungai Penuh City. This type of research is quasi-experimental, using a Randomized Control-Group Posttest Only Design. The population in this study were all Class VIII students for the 2021/2022 academic year. The sample in this study was selected using a random sampling technique. The results showed that the science learning outcomes of experimental class students using the PBL model obtained a higher average score than the control class using the direct learning model, with an average score of 79.94 for the experimental group and 70.82 for the control group. In conclusion, the PBL learning model influences the science learning outcomes of Class VIII students of SMP Negeri 10 Sungai Penuh. Keywords: Learning Outcomes, PBL, Students